Multidialectal and multilingual translanguaging in L2 Arabic classrooms: teachers’ beliefs vs. actual practices - Kawafha, Hazem; Al Masaeed, Khaled (Frontiers in Education, 2023)
This study adopts a multidialectal and multilingual translanguaging perspective to explore the relationship between beliefs and actual linguistic practices concerning multilingual and multidialectal practices among L2 Arabic teachers in Islamic independent schools in Sydney, Australia. To this end, the study draws on class observations and individual interviews. The findings show a clear mismatch between teachers’ beliefs about the use of English and their actual employment of it in the classroom. The majority of the teachers indicated that English should be either limited or totally avoided in the L2 Arabic classroom, but class observations showed that (a) English was utilized in all 11 classes, and (b) it was used significantly more than Arabic in 9 of these classes. As for multidialectal practices, although most of the teachers believed that the use of non-standard varieties along with Modern Standard Arabic (MSA) should be limited, findings were inconclusive due to the fact that English was found to be the main medium of communication in the majority of the observed classes. Therefore, the study underscores the need for providing teacher training that demonstrates how to purposefully deploy multilingual and multidialectal translanguaging to help learners enrich their linguistic repertoire in their desired L2.